Validitas Media Pembelajaran Menggunakan Aplikasi Focusky Dilengkapi Buku Panduan pada Materi Protista untuk Peserta Didik Kelas X SMA - Pratiwi Agatha; Armen; Sa'diatul Fuadiyah; Relsas Yogica (Department of Biology Education, Faculty of Education and teacher Training, Maritime University of Raja Ali Haji, 2019)
The availability and use of instructional media that fits the needs of students becomes a problem in learning biology at SMAN 2 Batang Anai, especially in protist material. This is due to the limited skills of teachers in obtaining and developing learning media according to the needs of students. One alternative problem is to develop learning media using the Focusky application equipped with a manufacturing manual. Focusky application will produce learning media that can stimulate students' learning styles with the advantages of drag and drop methods. The purpose of this study was to produce learning media using the Focusky application equipped with a guidebook on protist material for valid class X students. This research is development research (Research and Development) with the Instructional Development Institute (IDI) model which consists of the stages of defining, developing, and evaluating. The research subjects were two biology lecturers at FMIPA UNP and one biology teacher at SMAN 2 Batang Anai. The object of research is learning media using the Focusky application on protist material equipped with a guidebook for class X SMA students. The research data is primary data in the form of data validity which is obtained directly through the provision of validation questionnaires to the research subjects. Based on the results of the study produced learning media using the Focusky application on protist material equipped with a guidebook for students of class X that are valid with an average validity value of 88.82%. ABSTRAK: Ketersediaan dan penggunaan media pembelajaran yang sesuai dengan kebutuhan siswa menjadi masalah dalam pembelajaran biologi di SMAN 2 BatangAnai, terutama dalam materi protista. Hal ini disebabkan oleh keterbatasan keterampilan guru dalam memperoleh dan mengembangkan media pembelajaran sesuai dengan kebutuhan siswa. Salah satu masalah alternatif adalah mengembangkan media pembelajaran menggunakan aplikasi Focusky yang dilengkapi dengan manual manufaktur. Aplikasi Focusky akan menghasilkan media pembelajaran yang dapat merangsang gaya belajar siswa dengan keunggulan metode drag and drop. Tujuan dari penelitian ini adalah untuk menghasilkan media pembelajaran menggunakan aplikasi Focusky yang dilengkapi dengan buku panduan tentang bahan protista untuk siswa kelas X yang valid. Penelitian ini adalah penelitian pengembangan (Research and Development) dengan model Instructional Development Institute (IDI) yang terdiri dari tahapan mendefinisikan, mengembangkan, dan mengevaluasi. Subjek penelitian adalah dua dosen biologi di FMIPA UNP dan satu guru biologi di SMAN 2 BatangAnai. Objek penelitian adalah media pembelajaran dengan menggunakan aplikasi Focusky pada protista materi yang dilengkapi dengan buku panduan untuk siswa sekolah menengah kelas X. Data penelitian adalah data primer dalam bentuk validitas data yang diperoleh langsung melalui pemberian kuesioner validasi kepada subjek penelitian. Berdasarkan hasil penelitian dihasilkan media pembelajaran menggunakan aplikasi Focusky pada materi protist yang dilengkapi dengan buku pedoman untuk siswa kelas X yang valid dengan nilai validitas rata-rata 88,82%.